2014
DOI: 10.3390/ijms15035115
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 2-Aminobenzamide Derivatives as Antimicrobial Agents: Opening/Closing Pharmacophore Site

Abstract: A series of new 2-aminobenzamide derivatives (1–10) has been synthesized in good to excellent yields by adopting both conventional and/or a time-efficient microwave assisted methodologies starting from isatoic anhydride (ISA) and characterized on the basis of their physical, spectral and microanalytical data. Selected compounds of this series were then tested against various bacterial (Bacillus subtilis (RCMB 000107) and Staphylococcus aureus (RCMB 000106). Pseudomonas aeruginosa (RCMB 000102) and Escherichia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Several pharmacologically important compounds contain quinazoline nucleus as their basic framework [57]. Quinazoline derivatives have emerged as potential chemotherapeutic agents against solid tumors [59][60][61]. Several quinazoline derivatives like gefitinib, erlotinib, lapatinib, and afatinib have been approved by the FDA [62].…”
Section: Discussionmentioning
confidence: 99%
“…Several pharmacologically important compounds contain quinazoline nucleus as their basic framework [57]. Quinazoline derivatives have emerged as potential chemotherapeutic agents against solid tumors [59][60][61]. Several quinazoline derivatives like gefitinib, erlotinib, lapatinib, and afatinib have been approved by the FDA [62].…”
Section: Discussionmentioning
confidence: 99%
“…Halkalı bir anhidrid olan bileşik nükleofiller ile çok kolay reaksiyon verebilir [1]. Elde edilen ürünler boya, koku, tarım kimyasalları ve ilaç üretiminde kullanılır [2]. Ayrıca, kinazolinon ve kinazolindion gibi heterosiklik bileşiklerin sentezinde de rol oynar [3].…”
Section: Introductionunclassified
“…Compound 1 selectively inhibited E. coli with a MIC value of 16 μg/mL, which was comparable with the reference compound, streptomycin (MIC: 32 μg/mL). An overview of the literature revealed that the antimicrobial property of 2-aminobenzamide derivatives has been found for several compounds of this class which have been considered as potential agents for antimicrobial drug discovery [17]. Compounds 2 and 3 displayed inhibition against some test strains of both Gram-positive and Gram-negative bacteria, and against the yeast C. albicans (Table 3).…”
mentioning
confidence: 99%